Flat dispersion at large momentum transfer at the onset of exciton polariton formation - Hannah C. Nerl; Khairi Elyas; Zdravko Kochovski; Nahid Talebi; Christoph T. Koch; Katja Höflich (Communications Physics)
Abstract Excitons are quasiparticles, comprised of an electron excited from the valence band and attracted to the hole left behind, that govern transport properties in transition metal dichalcogenides. Excitonic coherence specifically needs to be understood to realise applications based on Bose-Einstein condensation and superfluidity. Here we used momentum-resolved electron energy-loss spectroscopy to obtain the complete energy-momentum dispersion of excitons in thin film and monolayer WSe 2 across the entire Brillouin zone, including outside of the light cone and for a large energy-loss range (1.5–4 eV). The measured dispersion of the modes was found to be flat. This suggests that the excitations are at the onset of polaritonic mode formation, propagating in the confinement of nanometer thin and monolayer WSe 2 . In combination with helium ion microscopy nanopatterning it was possible to probe and control these excitonic modes in thin film WSe 2 by modifying the local geometry through nanosized cuts.